2016
DOI: 10.1038/srep37341
|View full text |Cite
|
Sign up to set email alerts
|

Non-neutralizing antibodies induced by seasonal influenza vaccine prevent, not exacerbate A(H1N1)pdm09 disease

Abstract: The association of seasonal trivalent influenza vaccine (TIV) with increased infection by 2009 pandemic H1N1 (A(H1N1)pdm09) virus, initially observed in Canada, has elicited numerous investigations on the possibility of vaccine-associated enhanced disease, but the potential mechanisms remain largely unresolved. Here, we investigated if prior immunization with TIV enhanced disease upon A(H1N1)pdm09 infection in mice. We found that A(H1N1)pdm09 infection in TIV-immunized mice did not enhance the disease, as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…This is in line with recent observations in humans that also indicate that many influenza-specific antibodies, whether measured before or after vaccination, are cross-reactive (54, 55). Although serum antibodies induced by adjuvanted WIV were cross-reactive they could not neutralize heterologous and heterosubtypic virus in vitro , which was according to expectations (45, 56). Nevertheless, when transferred to naïve animals these antibodies provided partial protection against X-31 challenge.…”
Section: Discussionmentioning
confidence: 50%
“…This is in line with recent observations in humans that also indicate that many influenza-specific antibodies, whether measured before or after vaccination, are cross-reactive (54, 55). Although serum antibodies induced by adjuvanted WIV were cross-reactive they could not neutralize heterologous and heterosubtypic virus in vitro , which was according to expectations (45, 56). Nevertheless, when transferred to naïve animals these antibodies provided partial protection against X-31 challenge.…”
Section: Discussionmentioning
confidence: 50%
“…This ratio has been used to estimate the amount of “non-neutralizing antibody” present, 49,50 although the ability of neutralizing and non-neutralizing anti-influenza antibodies to actually protect against virus infection in vivo is poorly understood. 51,52 It is possible that repeated vaccination with inactivated influenza vaccine induces a population of antibodies that are suboptimal for protection. Further research is needed to better understand the specific subpopulations of antibodies induced by various influenza vaccination regimens, and how the different subpopulations interact with virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies in humans showed that the 2008-09 trivalent inactivated influenza vaccine could potentially enhance pandemic H1N1 infection and illness (Janjua et al, 2010; Skowronski et al, 2010). In a direct contrast, recent work in mice to evaluate these observations showed that pre-existing non-neutralizing antibodies after administration of TIV were not associated with enhanced disease, but in fact, they were shown to promote antigen presentation and activate virus-specific CD8 T cells (Kim et al, 2016). The difference between these observations in human and mice could be attributed to several factors including: difference in antibody types (classes) between the two species, titer of antibodies in the blood, the challenge model used in mice, and many others.…”
Section: Respiratory Viruses Enhanced Disease Illnessmentioning
confidence: 99%